Kekuatan pembuktian tanda tangan elektronik dalam suatu kontrak individual - Nurmawanadilah, Dita (Maliki Interdisciplinary Journal, 2024)
The purpose of this study is to find out how Electronic Signature proof should be regulated and how the law applies to civil disputes up to the status of Electronic Signatures. In Indonesian laws and regulations, the use of electronic signatures in contracts is now increasingly widely accepted and regulated. First, among others, in Law Number 11 of 2008 concerning Information and Electronic Transactions, which in Article 1 Number 12 states that "Electronic Signatures are signatures consisting of Electronic Information attached to, associated with, or related to other Electronic Information that used as a means of verification and authentication". However, despite having the ability to prove their innocence in court, many Indonesians are still not aware that electronic signatures are accepted by law as legal evidence. Therefore, the ability of electronic signatures as valid evidence in court must be understood and explained.